Telecommunication line infrastructure and the Arctic environment: past, present and future. (10th March 2021) - Saunavaara, Juha; Kylli, Ritva; Salminen, Mirva
Abstract: This article concentrates on the interconnected past, present and future of telecommunications and the environment in the Arctic. It brings together discussions on the natural environment, sustainable development and connectivity in and through the Arctic and focuses on fixed-line infrastructure. This study builds on the theoretical literature on infrastructure, infrastructuring and pipeline ecologies and demonstrates how the peculiar features of the Arctic, such as coldness, snow and ice, ground frost and permafrost affect telecommunication lines, and how this infrastructure impacts the environment in which it is built. Similarly, the environmental conditions, paired with long distances, small populations and limited economic opportunities, affect the infrastructuring processes and the selection of technologies, as well as their spatial extent, quality and the speed of their expansion. While the construction of telecommunication lines supports the exploitation of natural resources in and beyond the different parts of the circumpolar North, it also plays a role in the observation and protection of the Arctic.